Cold threat [large type] - Mehl, Nancy (Mehl, Nancy. Ryland & St. Clair (Series), 2024)
"Twenty years ago, several people were murdered in Des Moines, and the only evidence left behind was a snowman ornament hanging ominously on a tree in the victims' front lawns. With a suspect behind bars, the killings have come to an end -- or so everyone thought. But now crimes with a similar MO are happening in a small Iowa town, and a local detective believes the killer is back and ready to strike again. With little time left on the clock before they have another murder on their hands, private investigators River Ryland and Tony St. Clair must work alongside Tony's detective father to find evidence that will uncover an evil that has survived far too long. As the danger mounts and the suspect closes in, it will take all they have to catch a killer -- before he catches one of them."--